Three types of gall-bladder motility at men with chronic cholecystitis and pyelonephritis and accompanying their parameters of kidney excretory function as well as metabolism - Oksana M Ivanyts'ka; Tetyana G Fedun; Vitaliy G Velychko; Tetyana V Safyanyk; Svitlana L Popel; Halyna Y Dudra; Walery Zukow (Kazimierz Wielki University, 2018)
Background. Previously it has been shown that balneotherapy in the spa Truskavets' (Ukraїna) in men with chronic cholecystitis combined with pyelonephritis causes changes in gall-bladder motility. This is combined with changes in diurese and urinary excretion of metabolites.Individual analysis revealed not only quantitative but also qualitative differences in the postprandial motility of the gall-bladder. The purpose of this study is to identify the parameters of kidney excretory function as well as metabolism under which three types of the gall-bladdermotility skills differ significantly from each other. Materialandmethods. The object of observationwere the same ones 22men aged24-70 years old,who cameto the spaTruskavets' for the treatment of chronic cholecystitiscombined withpyelonephritis inremission. On thetone and motility of gall-bladder judged byits fasting and postprandial volume (echocamera "Radmir"). In the daily  determined content of oxalate and nitrogen metabolites: creatinine, urea and uric acid, electrolytes: phosphates, chloride, calcium, magnesium, potassium and sodium. Nitrogenous metabolites in plasma of venous blood were determined also. The survey was conducted twice, before and after balneotherapy. Results. The method of cluster analysis has formed three homogeneous cholekinetics groups, namely:normokinesia as well as hypertonic-hyperkinetic and hyperkinetic-hypertonic dyskinesia.The method of discriminatory analysis revealed 13 parameters of daily urine and three parameters of blood, as well as body weight and height, electrokinetic index and Kerdoe's index, in the totality of which three types of cholekinetics are clearly delineated.Conclusion. The type of postprandial cholekinetics is naturally associated with a number of parameters of the excretory renal function and metabolism.